2013
DOI: 10.1094/mpmi-01-13-0005-r
|View full text |Cite
|
Sign up to set email alerts
|

Host-Induced Gene Silencing in Barley Powdery Mildew Reveals a Class of Ribonuclease-Like Effectors

Abstract: Obligate biotrophic pathogens of plants must circumvent or counteract defenses to guarantee accommodation inside the host. To do so, they secrete a variety of effectors that regulate host immunity and facilitate the establishment of pathogen feeding structures called haustoria. The barley powdery mildew fungus Blumeria graminis f. sp. hordei produces a large number of proteins predicted to be secreted from haustoria. Fifty of these Blumeria effector candidates (BEC) were screened by host-induced gene silencing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
192
1
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(199 citation statements)
references
References 47 publications
4
192
1
2
Order By: Relevance
“…Therefore, an active secretion mechanism has been proposed that exports these CSEPs from the haustorium (22). Furthermore, although detailed biological roles of most CSEPs have not been documented, host-induced gene silencing (23) of some CSEPs suggested their role in host-defense suppression (24,25). Notably, the CSEP repertoire of Bgh is strikingly different from those of the distantly related Golovinomyces orontii and Erysiphe pisi powdery mildews, suggesting specific adaptations to their respective host plants (15).…”
Section: Significancementioning
confidence: 99%
“…Therefore, an active secretion mechanism has been proposed that exports these CSEPs from the haustorium (22). Furthermore, although detailed biological roles of most CSEPs have not been documented, host-induced gene silencing (23) of some CSEPs suggested their role in host-defense suppression (24,25). Notably, the CSEP repertoire of Bgh is strikingly different from those of the distantly related Golovinomyces orontii and Erysiphe pisi powdery mildews, suggesting specific adaptations to their respective host plants (15).…”
Section: Significancementioning
confidence: 99%
“…Host induced gene silencing (HIGS) is a relatively new approach for controlling plant pathogens that relies on RNA interference to target the expression of essential pathogen genes. This strategy has been used to target a wide range of pathogen types including insects (reviews by Baum et al 2007;Huvenne and Smagghe 2010), nematodes (reviewed by Huang et al 2006;Yadav et al 2006;Fairbairn et al 2007;Sindhu et al 2009), fungi (Nowara et al 2010;Tinoco et al 2010;Yin et al 2011;Zhang et al 2012;Koch et al 2013;Panwar et al 2013;Pliego et al 2013;Ghag et al 2014), parasitic weeds (Tomilov et al 2008), and oomycetes (Govindarajulu et al 2014;VegaArreguin et al 2014;Jahan et al 2015). Pathogen effectors essential for virulence or Bhousekeeping^genes necessary for normal pathogen growth are typically the targets for HIGS.…”
Section: Resistance To Biotic and Abiotic Stressesmentioning
confidence: 99%
“…HIGS phenomenon was first observed in barley-Bgh interaction (Nowara et al 2010) and now the idea has provided a method to investigate the role of pathogen genes (Pliego et al 2013). It also suggests a potential approach to engineering plants for resistance to PMs (Nowara et al 2010).…”
Section: Outlook On Breeding Perspectivesmentioning
confidence: 99%
“…In incompatible interactions (e.g., presence of Mla1 gene) the CSEPs expression decreases following a transcriptional reprogramming in barley epidermal cells and at the onset of cell death in those cells, suggesting a defence mechanism by which host suppresses production or secretion of pathogen's effectors (Hacquard, et al 2013). Functional analyses of 50 of these CSEPs showed that silencing of eight of them, which are similar to glucosyltransferases, metalloproteases, and microbial secreted ribonucleases, inside the pathogen compromised disease development (Pliego et al 2013). The ribonuclease-like effectors probably interfere with programed cell death in the host cells and, therefore, help establishment of pathogenicity (Pliego et al 2013).…”
Section: Pathogenomics: Powdery Mildew Effectorsmentioning
confidence: 99%
See 1 more Smart Citation